Competition over agents with boundedly rational expectations - Ran Spiegler (Theoretical Economics, 2006)
I study a market model in which profit-maximizing firms compete in multi-dimensional pricing strategies over a consumer, who is limited in his ability to grasp such complicated objects and therefore uses a sampling procedure to evaluate them. Firms respond to increased competition with an increased effort to obfuscate, rather than with more competitive pricing. As a result, consumer welfare is not enhanced and may even deteriorate. Specifically, when firms control both the price and the quality of each dimension, and there are diminishing returns to quality, increased competition implies an efficiency loss which is entirely borne by consumers.
Keywords: C79; D49; D83; 330; Bounded rationality; industrial organization; multi-dimensional pricing; law of small numbers; market exploitation; obfuscation